The Clue Of The Leaning Chimney - Keene Carolyn; Carolyn Keene (New York Carolyn Keene, 1967)
Nancy Drew investigates the theft of valuable Chinese vases and the kidnapping of a pottery expert, Eng Moy.
Keywords: The narrative follows Nancy as she attempts to solve the theft of a rare Chinese vase, with the titular "leaning chimney" serving as a critical landmark in her investigation; outward appearances can hide deep-seated corruption, and that diligence in investigating small, overlooked details can reveal the truth